Needs of people with disability and the participatory budget. Results of an opinion survey among Warsaw Muranów community - Krzywik, Adrianna; Nowakowska, Iwona (Understanding Disability: Issues, Research, Reflections, 2021)
The participatory budget in Warsaw is a form of citizen involvement in city planning. The projects submitted in the budget concern, among other things, the physical transformation of space, organizing events integrating the community, and educational programs. Each of the above categories may determine the inclusion of people with disabilities in society. Social inclusion in the perspective of city change is an interesting and still rarely researched phenomenon. This article is an analysis of the content of projects for people with disabilities submitted and implemented under the participatory budget in Warsaw in the years 2015–2020. On the basis of the collected material, a quantitative study was conducted and the results were used to formulate conclusions on how urban space is used and transformed through grassroots initiatives for people with disabilities. We present the scientific implications of the abovementioned analysis in the contexts of city sociology and environmental and rehabilitation psychology.